Studies in Demand: Milk and Butter - Gilboy, Elizabeth Waterman (Quarterly Journal of Economics, 1932)
I. Introduction — theoretical basis for deriving demand curves, 671. — II. Dealers' demand for butter, 675. — Final consumers' demand for butter, 681. — The part played by storage, 686. — III. Dealers' demand for milk, 690. — Elasticity, 693. — Shifting, 694. — Conclusion, a simple method for determining demand under certain conditions, 696.